SERCA Activity Controls the Systolic Calcium Increase in the Nucleus of Cardiac Myocytes - Kiess, Tobias-Oliver; Kockskämper, Jens (Frontiers in Physiology, 2019)
In cardiomyocytes, nuclear calcium is involved in regulation of transcription and, thus, remodelling. The cellular mechanisms regulating nuclear calcium, however, remain elusive. Therefore, the aim of this study was to identify and characterise the factors that regulate nuclear calcium in cardiomyocytes. We focused on the roles of (1) the cytoplasmic calcium transient (CaT), (2) the sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA) and (3) intracellular calcium stores for nuclear calcium handling. Experiments were performed on rat ventricular myocytes loaded with Fluo-4/AM. Subcellularly resolved CaTs were visualised using confocal microscopy. The cytoplasmic CaT was varied by reducing extracellular calcium (from 1.5 mM to 0.3 mM) or by exposure to isoprenaline (ISO, 10 nM). SERCA was blocked by thapsigargin (5 µM). There was a strict linear dependence of the nucleoplasmic CaT on the cytoplasmic CaT over a wide range of calcium concentrations. Increasing SERCA activity impaired, whereas decreasing SERCA activity augmented the systolic calcium increase in the nucleus. Perinuclear calcium store load, on the other hand, did not change with either 0.3 mM calcium or ISO and was not a decisive factor for the nucleoplasmic CaT. The results indicate, that the nucleoplasmic CaT is determined largely by the cytoplasmic CaT via diffusion of calcium through nuclear pores. They identify perinuclear SERCA activity, which limits the systolic calcium increase in the nucleus, as a novel regulator of the nuclear CaT in cardiac myocytes.